A review of the AURORA and BLISS trials: will it revolutionize the treatment of lupus nephritis?. Issue 3 (4th May 2022) - Asif, Sabaa; Bargman, Joanne; Auguste, Bourne
Abstract : Purpose of review: Renal involvement in patients with systemic lupus erythematosus can lead to significant complications including end-stage renal disease. Treatment of lupus nephritis has evolved over the last several decades, but despite this evolution, many patients fail to achieve remission and often progress to end-stage kidney disease or carry a burden of adverse side effects related to treatment. Recent findings: The recent findings from AURORA 1 and BLISS LN trials led the FDA to approve voclosporin and belimumab for the treatment of lupus nephritis. The AURORA 1 trial demonstrated that voclosporin, a second-generation calcineurin inhibitor, effectively lowers proteinuria in patients with lupus nephritis, when added to mycophenolate mofetil with a better safety profile, compared with other calcineurin inhibitors. The BLISS LN trial revealed better control of disease and lower risk of progression to end stage kidney disease (ESKD) and relapses in patients treated with belimumab in addition to standard therapy. Summary: Both voclosporin and belimumab are costly and have not shown any early evidence to revolutionize practice in the management of lupus nephritis. Until more data are made available with future studies or other cost-effective treatment options become available, the widespread adoption and utility of these novel agents remains limited.